2015
DOI: 10.1002/2015jb011939
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring changes in seismic velocity related to an ongoing rapid inflation event at Okmok volcano, Alaska

Abstract: Okmok is one of the most active volcanoes in the Aleutian Arc. In an effort to improve our ability to detect precursory activity leading to eruption at Okmok, we monitor a recent, and possibly ongoing, GPS‐inferred rapid inflation event at the volcano using ambient noise interferometry (ANI). Applying this method, we identify changes in seismic velocity outside of Okmok's caldera, which are related to the hydrologic cycle. Within the caldera, we observe decreases in seismic velocity that are associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Our results give an exclusive insight into the dynamics and the development of explosive and effusive eruptions, specifically when looking at the remarkable link between seismic velocity variation and ground deformation. Several existing studies have associated variations of seismic velocity and cycles of inflation and deflation with changes in magma pressurization (e.g., Brenguier et al, 2008;Bennington et al, 2015;Hotovec-Ellis et al, 2015;Donaldson et al, 2017). The compression associated with an increase in magma pressurization is expected to close pores and cracks in the medium, causing an increase of the elastic moduli and the seismic velocity, along with a potential inflation at the surface (O'Connell and Budiansky, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Our results give an exclusive insight into the dynamics and the development of explosive and effusive eruptions, specifically when looking at the remarkable link between seismic velocity variation and ground deformation. Several existing studies have associated variations of seismic velocity and cycles of inflation and deflation with changes in magma pressurization (e.g., Brenguier et al, 2008;Bennington et al, 2015;Hotovec-Ellis et al, 2015;Donaldson et al, 2017). The compression associated with an increase in magma pressurization is expected to close pores and cracks in the medium, causing an increase of the elastic moduli and the seismic velocity, along with a potential inflation at the surface (O'Connell and Budiansky, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Ambient noise studies do not require an active source or repeating earthquakes and have been successfully applied to measure changes in seismic velocity in a range of different environments, such as volcanoes Donaldson et al, 2017;Sánchez-Pastor et al, 2018;Sens-Schönfelder & Wegler, 2006), landslides (Mainsant et al, 2012), underground mines , geothermal reservoirs (Hillers et al, 2015;Obermann et al, 2015), active faults zones , earthen dams (Olivier et al, 2017;Planès et al, 2015), and other environments. Notably, it has been shown that a detectable change in seismic velocity occurs in the days leading up to an eruption at some volcanoes (Bennington et al, 2015;Budi-Santoso & Lesage, 2016;Caudron et al, 2015;Grêt et al, 2005;Hirose et al, 2017;Patanè et al, 2006;Ratdomopurbo & Poupinet, 1995;Wegler et al, 2006). These virtual source signals can be constructed at different times, so small temporal changes in seismic velocity can be measured to study processes in the Earth's crust.…”
Section: Methodsmentioning
confidence: 99%
“…These virtual source signals can be constructed at different times, so small temporal changes in seismic velocity can be measured to study processes in the Earth's crust. Notably, it has been shown that a detectable change in seismic velocity occurs in the days leading up to an eruption at some volcanoes (Bennington et al, 2015;Budi-Santoso & Lesage, 2016;Caudron et al, 2015;Grêt et al, 2005;Hirose et al, 2017;Patanè et al, 2006;Ratdomopurbo & Poupinet, 1995;Wegler et al, 2006). Authors in these studies attribute precursory velocity changes to the dilation/compression of the edifice due to the increased pressure the magma chamber exerts on the edifice, which has been shown to cause measurable changes in seismic velocities at volcanoes (Sens-Schönfelder et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…For the set of NCFs associated with the 2004 and 2013 eruptions at Veniaminof, narrow frequency band ANI analyses yielded wildly varying changes in seismic velocity with large associated error bars. Thus, we cannot apply the same methodology as Lesage et al (2014) and Bennington et al (2015). We present an alternative approach to estimate the frequency at which changes in seismic velocity occur in the time leading to eruption.…”
Section: Frequency Analysis Of the 2013 Eruptionmentioning
confidence: 99%
“…First, we utilize the technique of ambient noise interferometry (ANI), which detects subtle changes in seismic velocity associated with changes in the material properties of the subsurface. ANI has become a well‐established technique for identifying magmatic activity at active volcanoes (e.g., Bennington et al, ; Brenguier et al, ; Budi‐Santoso & Lesage, ; Duputel et al, ; Haney et al, ; Mordret et al, ; Obermann et al, ). This method typically uses ambient noise data derived from pairs of seismic stations; however, Haney et al () and De Plaen et al () demonstrate that changes in seismic velocity can also be determined using ambient noise data determined from individual stations.…”
Section: Introductionmentioning
confidence: 99%